Learning to write short stories with self-regulation strategy development (SRSD) and text song - Seni Asiati (Universitas Indraprasta PGRI, 2017)
This classroom action research aims to improve the skills of writing short stories in junior high school students with strategies SRSD and song texts. The issues are the focus of study in this research is; Do SRSD and song texts can improve learning students' writing? From the analysis of the data, the conclusions obtained from this research is to increase the ability of students to write short stories with SRSD and text tracks that can be seen from the increasing student learning outcomes. It can be seen from the evidence of quantitative and qualitative evidence. Quantitative evidence: the value of students who achieve KKM 34 students (94%), student scores less than KKM 2 students (5.5%). There was an increase of 80.2% from the first cycle and the second cycle. Qualitative evidence shows: (1) the student is doing the learning beminat (2) students are more daring expression (3) the learning environment more natural and fun. Observation of the students do in school activity. Evidence suggests that learning to write short stories SRSD and text can be used to improve the ability to write short stories.